Antibiotic Resistance Case Study: Enterobacteriaceae isolated from Batlama Creek in Giresun, Turkey - Tamer Akkan (Turkish Journal of Agriculture: Food Science and Technology)
Enterobacteriaceae were isolated from the freshwater of the Batlama Creek in Giresun, to measure their resistance levels against to antibiotics. A total of 9 antibiotics disc were applied for the resistance test. Antibiotic resistances of all isolates were at percentages for ampicillin (75%), erythromycin (64%), nalidixic acid (48%), tetracycline (39%), amikacin (34%), cefazolin and chloramphenicol (33%), cefuroxime (32%) and cefotaxime (23%), respectively. The highest resistant strain was resistant against to 9 antibiotics, while the weak resistance of 16 isolates were sensitive to all antibiotics. Moreover, Multiple antibiotic resistance index values were found to be higher than 0.2 for 77% of all isolates. High resistances of examined bacteria against to antibiotics indicated a dense and multisource pollution in the Batlama Creek. Consequently, a need for good surveillance programs to monitor antimicrobial resistance patterns in surface water bodies.